Charge Redistribution Effects in Hexacyanometallates Evaluated from XPS Data. Issue 1 (17th December 2019) - Cano, Arely; Reguera, Leslie; Avila, Manuel; Velasco‐Arias, Donaji; Reguera, Edilso
Abstract : The charge redistribution effects determine the physical and functional properties of transition metal hexacyanometallates. The π‐back bonding interaction between the CN ligand and the metal (M) linked at its C end and the σ donation from the N end to a second transition metal (T), when a coordination polymer is formed, are relevant features of such effects. The π‐back donation interaction contributes to the overlapping of the electron clouds of M and T metals in the ··· –T–N≡C–M–C≡N–T‐··· chain. In this contribution, we demonstrate that XPS spectroscopy is a useful tool to sense the change in the electron density redistribution in hexacyanometallates related to these two mechanisms. The results herein discussed contribute to understand the physical and chemical properties of these materials. Initially, a series of potassium salts, Kn [M 6–n (CN)6 ] (M = Cr III, Fe II, Ru II, Os II, Co III, Rh III, Ir III, Pt IV ) is considered in order to evaluate the role of the π‐back donation on the electron density found at the N atom, which determines the strength for the T‐NC coordination bond and of the mentioned electron clouds overlapping. Then, a representative set of transition metal (T) hexacyanometallates, T2(1‐ y) K2 y [Fe II (CN)6 ], is studied in order to shed light on the electron density redistribution when a coordination bond is formed at the N end. Within such coordination polymers, the copper (2+) salts are particularly attractive by the unique interaction between the copper atom and the hexacyanometallate ion, and the potential applications of these copper (2+) complexes in heterogeneous catalysis and other areas. From these reasons, the recorded XPS spectra for Cu (2+) hexacyanometallates were evaluated in detail. In accordance with a previous study of these copper (2+) coordination polymers using other techniques, XPS data is sensing an atypical strong bonding interaction with the CN ligand. The experimental XPS data herein discussed are relevant for the coordination chemistry of transition metal hexacyanometallates and for the research community involved in their applications. Abstract : Charge redistribution effects in hexacyanometallates according to XPS spectra. This technique can map the change in the electron density related to both the π‐back donation effect and the coordination bond formation at the N end of the CN ligand, using the N 1s core‐level binding energy as sensor.